Cyber-based structure elucidation - Munk, Morton E. (Henry Stewart Talks, 2011)
Importance in drug discovery, Structure elucidation as old as chemistry itself, Role of the Computer; Augment productivity and reliability, Computer Capabilities: Spectrum interpretation, structure generation, spectrum prediction and spectrum comparison, Program SESAMI: A compressive structure elucidation system, SESAMI: Problem solving, Stereochemistry